What do Veterans with homeless experience want us to know that we are not asking? A qualitative content analysis of comments from a national survey of healthcare experience. (22nd July 2022) - Varley, Allyson L.; Hoge, April; Riggs, Kevin R.; deRussy, Aerin; Jones, Audrey L.; Austin, Erika L.; Gabrielian, Sonya; Gelberg, Lillian; Gordon, Adam J.; Blosnich, John R.; Montgomery, Ann Elizabeth; Kertesz, Stefan G.
Abstract: Surveys of people who experience homelessness can portray their life and healthcare experiences with a level of statistical precision; however, few have explored how the very same surveys can deliver qualitative insights as well. In responding to surveys, people experiencing homelessness can use the margins to highlight health and social concerns that investigators failed to anticipate that standard question batteries miss. This study describes the unprompted comments of a large national survey of Veterans with homeless experiences. The Primary Care Quality‐Homeless Services Tailoring (PCQ‐HOST) survey presented 85 close‐ended items to solicit social and psychological experiences, health conditions, and patient ratings of primary care. Amongst 5377 Veterans responding to the paper survey, 657 (12%) offered 1933 unprompted comments across nearly all domains queried. Using a team‐based content analysis approach, we coded and organised survey comments by survey domain, and identified emergent themes. Respondents used comments for many purposes. They noted when questions called for more nuanced responses than those allowed, especially 'sometimes' or 'not applicable' on sensitive questions, such as substance use, where recovery status was not queried. On such matters, the options of 'no' and 'yes' failed to capture important contextual and historical information that mattered to respondents, such as being in recovery. Respondents also elaborated on negative and positive care experiences, often naming specific clinics or clinicians. This study highlights the degree to which members of vulnerable populations, who participate in survey research, want researchers to know the reasons behind their responses and topics (like chronic pain and substance use disorders) that could benefit from open‐ended response options. Understanding patient perspectives can help improve care. Quantitative data from surveys can provide statistical precision but may miss key patient perspectives. The content that patients write into survey margins can highlight shortfalls of a survey and point towards future areas of inquiry. Veterans with homeless experience want to provide additional detail about their lives and care experiences in ways that transcend the boundaries of close‐ended survey questions. Questions on substance use proved especially likely to draw comments that went beyond the permitted response options, often to declare that the respondent was in recovery. Respondents frequently clarified aspects of their care experiences related to pain, pain care, transportation and experiences of homelessness.